Therapy of nodal Follicular Lymphoma (WHO grade 1/2) in clinical stage I/II using response adapted Involved Site Radiotherapy in combination with Obinutuzumab (Gazyvaro) - GAZAI Trial (GAZyvaro and response adapted Involved-site Radiotherapy): a study protocol for a single-arm, non-randomized, open, national, multi-center phase II trial - König, Laila; Dreyling, Martin; Dürig, Jan; Engelhardt-Schagen, Marianne; Hohloch, Karin; Viardot, Andreas; Witzens-Harig, Mathias; Kieser, Meinhard; Klapper, Wolfram; Pott, Christiane; Herfarth, Klaus (Trials, 2019)
Large field irradiation had been standard for early-stage follicular lymphoma (FL) for a long time. Although involved field radiotherapy (IF-RT) was recently favored because of the toxicity of large field irradiation, smaller irradiation fields have been accompanied with an increased risk of out-of-field recurrence. The MIR (MabThera® and Involved field Radiation) trial has shown that the combination of IF-RT at a dose of 30-40 Gy with the anti-CD20 antibody rituximab has led to similar efficacy compared with large field irradiation but with markedly reduced side effects. Immune modulating radiation therapy alone using low-dose radiotherapy (LDRT) of 2 × 2 Gy has been shown to be effective in FL. The GAZAI (GAZyvaro and response Adapted Involved-site Radiotherapy) trial aims to prove the efficacy of LDRT in combination with a novel anti-CD20 therapy.